Investor Sentiment, Market Volatility, and IPO Initial Returns - Soeroto, Wisudanto Mas; Saputra, Sahdan; Arifin, Vanesa Aristanti; Hasina, Zahwaril; Putri, Tri Veny (Jurnal Keuangan dan Perbankan, 2021)
This research seeks to determine the impact of investor sentiment and market volatility on IPO initial return when an issuer conducts an Initial Public Offering (IPO). This research lasted ten years, from 2009 to 2020, with a total issuer of 237 conducting Initial Public Offerings (IPOs) on the Indonesia Stock Exchange. The total number of issuers conducting an initial public offering (IPO) met the purposive sampling criteria is 285. Multiple linear regression analysis, with control variables such as Gap of Days, Firm Age, IPO Size, and Firm Size, is used to determine the effect of Investor Sentiment and Market Volatility on IPO Initial Returns. The findings showed that Investor Sentiment and Market Volatility positively affected the IPO Initial Return during the study period. This research aims to increase investor awareness of the importance of IPO stock price, increasing the initial return in the future. In Indonesia, Otoritas Jasa Keuangan (OJK) plays a critical role in policies that facilitate Indonesian investors' monitoring of the volatility of stock price changes in the market.JEL: M2, M21